(untitled) (Iraqi Journal of Medical Sciences, 2020)
Background: Spirometry is a physiological procedure used as a diagnostic tool for disease diagnosis; e.g. obstructive pulmonary diseases such as asthma or chronic obstructive pulmonary disease (COPD). The bronchodilator test is a method of measuring lung capacity changes following inhalation of a short-acting bronchodilator drug that dilates the airway, this test helps to diagnose, evaluate and differentiate asthma from COPD. Objective: To evaluate the role of forced expiratory volume in third second (FEV3) as an alternative for forced vital capacity (FVC) in assessing bronchodilator response in patients with chronic obstructive airway diseases. Methods: The study a case-control, comparative study done from November 2018 to November 2019. The cases involved divided into 2 groups; patients group included (80) patients with chronic obstructed pulmonary diseases (asthma and COPD) and control group included (160) apparently healthy peoples aged and sex matched. Lung function was measured using a standard protocol and electronic table spirometry. Bronchodilator test was done for each patient with chronic obstructed defect on spirometer. Results: There was no significant difference between (FVC), FVC% and (FEV3), FEV3% respectively before bronchodilator and there was no significant difference after bronchodilator in patients. There was no significant difference between FEV1/FVC, FEV1/FVC % and FEV1/ FEV3, FEV1/FEV3% respectively before bronchodilator and there was no significant difference after bronchodilator in patients. Conclusion: FEV3 can be used as an alternative to FVC in patients with chronic obstructive airway diseases for assessing bronchodilator response. Keywords: Spirometry, Bronchodilator test, FVC%, FEV3%, FEV1/FVC%, FEV1/FEV3% Citation: Jizar AY, Hashim ZH, Jasim AH. Role of forced expiratory volume in third second (FEV3) as an alternative to forced vital capacity (FVC) in assessing bronchodilator response in patients with chronic obstructive airway diseases. Iraqi JMS. 2020; 18(2): 94-100. doi: 10.22578/IJMS.18.2.2